Eye Protection in ENT Practice During the COVID-19 Pandemic. Issue 2 (April 2021) - Ng, Jia Hui; Daniel, Dan; Sadovoy, Anton; Teo, Constance Ee Hoon
Objectives: There is a lack of evidence-based guidelines with regard to eye protection for aerosol-generating procedures in otolaryngology practice. In addition, some recommended personal protective equipment (PPE) is not compatible with commonly used ENT equipment. This study aims to investigate the degree of eye protection that commonly used PPE gives. Study Design: Simulation model. Setting: Simulation laboratory. Methods: A custom-built setup was utilized to simulate the clinical scenario of a patient cough in proximity of a health care worker. A system that sprays a xanthan-fluorescein mixture was set up and calibrated to simulate a human cough. A mannequin with cellulose paper placed on its forehead, eyes, and mouth was fitted with various PPE combinations and exposed to the simulated cough. The degree of contamination on the cellulose papers was quantified with a fluorescent microscope able to detect aerosols ≥10 µm. Results: When no eye protection was worn, 278 droplets/aerosols reached the eye area. The use of the surgical mask with an attached upward-facing shield alone resulted in only 2 droplets/aerosols reaching the eye area. In this experiment, safety glasses and goggles performed equally, as the addition of either brought the number of droplets/aerosols reaching the eye down to 0. Conclusion: When used with an upward-facing face shield, there was no difference in the eye protection rendered by safety goggles or glasses in this study. Safety glasses may be considered a viable alternative to safety goggles in aerosol-generating procedures.